Investigation on damaged planar-oxide of 1200 V SiC power MOSFETs in non-destructive short-circuit operation. (September 2017) - Boige, F.; Richardeau, F.; Trémouilles, D.; Lefebvre, S.; Guibaud, G.
Abstract: The purpose of this paper is to present an extensive study of three 1200 V silicon carbide (SiC) Power MOSFETs in non-destructive, but leading to degradations, short-circuit operation. Unusually, as compared with equivalent device built on silicon, the damage signature is a significant gate current increase but the components are still functional. In order to find the damage location, non-destructive and destructive methods have been carried out. The results converge to a local gate oxide breakdown caused by the important electrical and thermal stress during short-circuit operation leading to different failure mechanisms depending on the device design.